Neologisms in American Electronic Mass Media; Advances in Intelligent Systems and Computing; Vol. 677 : Linguistic and Cultural Studies: Traditions and Innovations, (LKTI 2017) - Martseva T. A. Tatiana Aleksandrovna; Snisar A. Y. Anastasiya Yurjevna; Kobenko Yu. V. Yury Viktorovich; Girfanova K. A. Kseniya Andreevna (Linguistic Studies, 2017)
Title screen